De Homokrant : voor vrouwen en mannen. - Federatie Werkgroepen Homofilie (FWH) (Antwerpen : FWH, 1979)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : Atletiekplein 4, 9000 Gent ; vanaf 10(1984) 6 : Dambruggestraat 204, 2000 Antwerpen
Nederlands
Periodiek